Penerapan Doktrin Vicarious Liability pada Holding Company atas Kejahatan Algoritma Pasar Digital oleh Anak Perusahaan - Phani Annisatul Hidayah; Imas Ummu Salamah; Abdul Fatah; Deni Muharamdani; Diki Ahmad (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2026)
The evolution of digital business ecosystems structured around holding and subsidiary relationships raises issues regarding criminal liability when crimes involving artificial intelligence (AI) algorithms—executed by a subsidiary—result in harm, while the parent company seeks refuge behind the principle of separate legal personality. This study aims to reconstruct the application of the doctrine of vicarious liability to holding companies regarding algorithmic crimes committed by their subsidiaries. Employing a normative-juridical method, the research utilizes statutory, conceptual, and case-based approaches to analyze regulations and court rulings concerning corporate criminal liability. The findings indicate that a holding company may be held criminally liable if it is proven to have exercised control, derived economic benefits, and failed to implement adequate oversight mechanisms regarding the subsidiary's use of algorithms. Consequently, there is a need to strengthen regulations defining the parameters of holding company criminal liability within the ecosystem of digital crime.